2018
DOI: 10.1515/gcc-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

The word problem of ℤ n is a multiple context-free language

Abstract: The word problem of a group {G=\langle\Sigma\rangle} can be defined as the set of formal words in {\Sigma^{*}} that represent the identity in G. When viewed as formal languages, this gives a strong connection between classes of groups and classes of formal languages. For exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The genus 0 surface (the sphere) gives us the trivial group, and 1 (the torus), Z 2 (see for example [21]). We know both of these groups are regular, 2-MCF [16], respectively, so certainly PHRS (Theorem 3.17).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The genus 0 surface (the sphere) gives us the trivial group, and 1 (the torus), Z 2 (see for example [21]). We know both of these groups are regular, 2-MCF [16], respectively, so certainly PHRS (Theorem 3.17).…”
Section: Discussionmentioning
confidence: 90%
“…The multiple context-free (MCF) languages sit strictly in between the context-free and context-sensitive languages [29]. In 2015, a major breakthrough of Salvati was published, showing that the word problem of Z 2 is an MCF language [28], and in 2018, Ho extended this result to all finitely generated virtually Abelian groups [16]. This is interesting since the MCF languages are exactly the string languages generated by hyperedge replacement grammars [10,31].…”
Section: Introductionmentioning
confidence: 99%
“…Meng-Che Ho [17] has recently shown that the word problem of Z n is MCF for all n. Hence by Lemma 3 all finitely generated virtually abelian groups have MCF word problems. We have the following corollary to Theorem 5.…”
Section: Introductionmentioning
confidence: 81%
“…A multiple context-free grammar is a quadruple G = (N, Σ, P, S), where N is a finite ranked set of non-terminals, Σ is an alphabet, P is a finite set of production rules over (N, Σ) and S ∈ N (1) is the start symbol. We call G m-multiple context-free or a m-MCFG, if the rank of all non-terminals is at most m.…”
Section: Definitions and Notationmentioning
confidence: 99%